Application of Islamic Values in the Application of Human Resource Management Practices (Studies in Islamic Hospital Fatimah Employees Cilacap) - Rizki Indah Kartikasari; Mirwan Surya Perdhana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Management is a product of community culture. Management practices that are successful in a country or a company may not necessarily be applicable elsewhere due to differences in culture and values. Indonesia is a country with a Muslim majority, so Islamic values are part of the lives of Indonesian Muslims, one of which is in the process of implementing Islamic Work Values (IWV) in the workplace. This study will discuss the application of Islamic values in the practice of Human Resource Management and how important it is to apply these Islamic values in the workplace. The data collection method in this study used an interview technique conducted with 5 employees at the Fatimah Islamic Hospital in Cilacap. The method used is a qualitative method with a phenomenological approach. The results in this study indicate that the application of the values of trust and responsibility, fairness, Ihsan, mutual assistance, and deliberation have been implemented well in the practice of Human Resource Management. All of the informants felt that applying Islamic values in the workplace could improve their quality, create a feeling of security, comfort, and increase morale as well as a reminder to align their intentions and goals at work.